Advances in the synthesis and properties of sulfur quantum dots for food safety detection and antibacterial applications - Huang, Yihong; Liu, Yujia; Fu, Ning; Huang, Qitong; Zhang, Hanqiang (Food chemistry, 2025)
Food safety is closely related to human health and has become a worldwide, pressing concern. Food safety analysis is essential for ensuring food safety. Sulfur quantum dots (SQDs), a new type of zero-dimensional metal-free nanomaterials, have recently become the focus of scientific research due to their good luminescence properties, dispersibility, biocompatibility, and inherent antibacterial properties. This review focuses on recent advances in SQDs, with emphasis on their practical applications in the food field. First, commonly used methods for the synthesis of SQDs are presented, including traditional and emerging strategies. The properties of SQDs are then analyzed in detail, particularly their luminescence properties, catalytic activities, and reducing properties. Next, the use of SQDs in food safety detection and antibacterial fields are elaborated. Finally, this review discusses the challenges associated with the use of SQDs in food safety detection and antimicrobial applications. Illustration of the synthesis methods and properties analysis of SQDs and their application in the food field. [Display omitted] •SQDs have promising applications in food safety detection and antibacterial fields.•The synthesis and properties of SQDs are discussed in detail.•Applications of SQDs in food safety detection and antibacterial fields are summarized.•Challenges, perspectives, and prospects of SQDs in the food field are proposed.